Nonattenuated Polymyxin B Used for the Treatment of Extreme-Drug Resistant Acinetobacter baumannii-Related Infections in Patients with Preexisting End Stage Renal Failure - Yvonne Peijun Zhou; Nathalie Grace Sy Chua; Maciej Piotr Chlebicki; Winnie Hui Ling Lee; Andrea Lay Hoon Kwa (Case Reports in Infectious Diseases)
Recent pharmacokinetic studies have suggested that nonrenal clearance predominates the elimination of polymyxin B. We present 2 patients with preexisting end stage renal failure, who were given nonattenuated doses of polymyxin B for the treatment of extreme-drug resistant organism. No evidence of adverse events occurred and microbiological clearance was documented.